Appreciative Leadership: Supporting Education Innovation - Orr, Tracy; Cleveland-Innes, Marti (International Review of Research in Open and Distributed Learning, 2015)
Appreciative Leadership is unique among leadership theories both past and present. This uniqueness includes its strength-based practice, search for the positive in people and organizations, and the role this plays in organizational innovation and transformation. What follows is a summary of Appreciative Inquiry and the five main principles on which it is based. We then discuss Appreciative Leadership in terms of its place among leadership theories in general. Finally we look at the potential of Appreciative Leadership in K-12 contexts.